The Relationship of Agility and Eye Coordination Feet on Dribbling Skills In Football Game Class XI Students of SMAN 2 Kampar - Jufrianis Jufrianis; Desliangga Anugrah; Mohammad Fauziddin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research aims to determine the relationship between agility and eye-foot coordination on dribbling ability in class XI football at SMAN 2 Kampar. This type of research is correlational. The population in this study were class XI students of SMAN 2 Kampar, sampling with a total sampling of 60 students. The instruments used in this research were agility tests using base stick agility, eye-foot coordination using the football wall volleyball test, and dribbling using the ball dribbling test. Data were analyzed using product moment correlation and continued with multiple correlation coefficients. Based on the results of data analysis, it shows that: There is a significant relationship between agility and eye-foot coordination on dribbling the ball in class. The coefficient of determination (R2) in the multiple regression analysis of two predictors is 17.54. This means that it has a relationship of 17.54%.